Upaya Penanggulangan Kemiskinan di Tulungagung Melalui Pemberdayaan Usaha Mikro Kecil dan Menengah (UMKM) - Halawa, Yarfika; Rindrayani, Sulastri Rini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Poverty is a very serious problem that must be addressed immediately, which plays an important role in alleviating poverty is the government and also the community itself. The purpose of this research is to find out how efforts to empower MSMEs in Tulungagung to reduce poverty levels. The method used by the author in this research is Study Literature Review or systematic literature review. The Study Literature Review method is a research and development method used to collect and evaluate research on a particular topic. The efforts made by the government are to increase access to capital, provide training and assistance to the community and improve infrastructure and facilities for opening a business, so as to increase competitiveness among entrepreneurs in Tulungagung Regency and make it easier for MSME entrepreneurs to open a business.